A finite element-peridynamic combined multiscale analysis strategy based on implicit integration scheme. (November 2022) - Zhang, Ning; Zheng, Yue; Wu, Honglei; You, Xin; Chen, Jiawei
Abstract: Although peridynamics (PD) method can address discontinuity issues existing in civil engineering, it is much more computationally expensive than the conventional finite element (FE) method because of inherent shortcomings such as small grid spacing and explicit integration scheme. In this regard, a multiscale analysis method reformulated in an implicit integration scheme, named FE-PD method, is proposed, which integrates the PD method with the FE method to take the advantages of discontinuity solving capacity of the PD method and high computing efficiency of the FE method. This study commences with the introduction of the bond-based PD theory. Subsequently, the framework of the FE-PD method together with two newly developed interface elements is presented. Finally, how to implement the FE-PD method into an open-source FE software, OpenSees, is illustrated, and the proposed FE-PD method is verified by a benchmark problem involving an l -shaped concrete plate sustaining a vertical loading, as well as a 2D and a 3D cantilever beam sustaining uniaxial tensile and shear loadings, respectively. Besides, the FE-PD method is employed to simulate the bond-slip behavior of the rebar embedded in a solid concrete specimen. The investigation results confirm that the FE-PD method not only consumes relatively much less (e.g., about 70%) computing resources compared with the PD method but also well captures the crack propagation of concrete and the bond-slip behavior of the rebar embedded in a quasi-brittle concrete specimen.